Hubungan antara Kadar Feritin dengan Kadar BUN-Kreatinin pada Pasien Talasemia Beta Mayor di RSD dr. Soebandi Jember (The Correlation between Ferritin Levels and BUN-Creatinine Levels of Major Beta Thalassemia Patients at dr. Soebandi Hospital Jember) - Kurnia Elka Vidyarni; Mohamad Ali Shodikin; Rini Riyanti (Pustaka Kesehatan, 2017)
Major beta thalassemia patients with iron overload will have increase on ferritin levels. Free iron can cause damage in several organs including kidney. One of parameter used to investigate the function of kidney is BUN and creatinine. This study was aimed to determine the correlation between ferritin levels and BUN-creatinine levels of major beta thalassemia patients at dr. Soebandi Hospital Jember. This is an analytical observational study with cross sectional study design, using 15 patients of thalassemia at the Paediatrics Department of dr. Soebandi Hospital Jember who met inclusion criteria. The data was obtained from medical records or patients report book. Data was analyzed with Shapiro Wilk normality test and Spearman correlation test. The mean of ferritin levels was 3.145±57,99 ng/mL, BUN levels was 8,87±1,18 mg/dL, and creatinine levels was 0,53±0,24 mg/dL. The Spearman correlation test for the correlation between ferritin levels and BUN levels showed r=0,073 and p=0,795 and the correlation between ferritin levels and creatinine levels resulted r=0,173 and p=0,537. In conclusion, there was no correlation between ferritin levels and BUN-creatinine levels of major beta thalassemia patients at the dr. Soebandi hospital Jember. Keywords: thalassemia, ferritin, BUN, creatinine